Transmission and Reception of Arabic Grammatical Knowledge: A Study of the Works of Traditional Islamic Boarding School Scholars of the Syarah Kitab al-Jurumiyyah in Local Language in Cirebon, West Java - Mahmudah; Muhammad Irfai Muslim (Indonesian Journal of Arabic Studies, 2026)
Purpose — This study examines the transmission and reception of Arabic grammatical knowledge within the pesantren tradition of Cirebon through an in-depth analysis of three locally written commentaries (sharḥ) on al-Jurumiyyah: Zubdat an-Naqiyyah by KH Aqil Siroj (Kempek), Tahrīran Jurūmiyyah by KH Muhammad (Kebon Jambu), and Tahrīrān al-Jurūmiyyah by KH Asmawi (Az-Ziyadah). The research is motivated by the strong tradition of instrumental sciences (ʿilm al-ālah—particularly naḥw and ṣarf) in Cirebon’s salafiyah pesantren, which historically functioned as key centers for the pedagogy of kitab kuning in West Java. Design/Method/Approach — Employing an applied philological approach, reception analysis, and educational ethnography, this study traces the chains of scholarly transmission, the structural characteristics of local sharḥ compositions, and the pedagogical strategies implemented through bandongan, sorogan, lalaran, and oral–written examinations. Findings — The findings reveal that vernacular sharḥ functions both as an instructional tool facilitating comprehension of classical Arabic texts and as a form of vernacularization of Arabic grammar that demonstrates pesantren scholars’ capacity for local intellectual reproduction. Pedagogical technologies such as makna gandul (symbolic markers such as ر, ن, ج), contextual iʿrāb examples, applicative explanations, and Cirebonese idioms significantly assist beginner students in internalizing grammatical principles. Research Implications — This study concludes that the Cirebonese local sharḥ tradition plays a significant role in preserving the continuity of the classical naḥw curriculum while simultaneously enriching context-based models of Arabic grammatical learning within the pesantren educational system.